Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The Impact of Psychological Factors on the Purchasing Desire Among Members of the Saudi Society In the period between 2021 - 2023 AD Mr. Bandar Abdul-Rahim Al-Ghamdi 2. The extent to which Palestinian audit offices comply with the requirements of the International Standard for Quality Management (ISQM 1) Ms. Etedal Robeen Siaj 3. The impact of administrative creativity in consolidating organizational culture in private schools in the Holy Capital Ms. Ghaliah Habibullah Turkstany 4. The impact of the audit committee on the disclosure of intellectual capital An applied study in Sudanese industrial companies Mr. Sabi Mahmood Abdullah, Co-Prof. Mohamed Elnair Mohamed Elnour 5. The Role of Human Resources Strategy in Achieving Professional Growth in Private Universities Considering Vision 2030 Asst-Prof. Salma Mohammed Jaghoubi, Ms. Sarah Abdullah Owayyid 6. Strategic analysis of human resources management in its work to enhance organizational performance in the telecommunications sector, Kingdom of Saudi Arabia Dr. Sadiq Ali Al-Shuwaikhat, Dr. Haya Ibrahim Al Tuwaym, Dr. Sara Saad Al-Dawsari 7. Employees Empowerment and its Relationship to Competitive Advantage A Case Study / Hotel Sector / Sultanate of Oman Mr. Khalaf Sulaiman Albahri 8. Commitment to conformity in the international sales contract Dr. Muneer Ali Hulaiel